The Digital Influence: Exploring the Impact of E-Marketing Techniques on Tiktok Users' Purchase Decisions - Hidayah*, Nurul; Nurrohim, Hasa (JURISMA : Jurnal Riset Bisnis & Manajemen, 2023)
This research aims to examine the influence of E-Marketing, namely Influencer Marketing, Content Marketing, and User-Generated Content on TikTok users in Daerah Istimewa Yogyakarta regarding their purchase decisions. The criteria for this research include TikTok users aged 18-34 residing in Daerah Istimewa Yogyakarta. The technique used to gather the sample is purposive sampling, and data is collected through an online questionnaire from 100 respondents. The research follows a descriptive analysis with a quantitative approach, and data analysis is conducted using Partial Least Square (PLS) with the data management program Smart PLS 3.0. The results of this study show that influencer marketing has a positive and significant effect on purchase decisions, content marketing similarly has a positive and significant effect on purchase decisions, and user-generated content also positively and significantly influences purchase decisions.Keywords: E-Marketing; Influencer Marketing; Content Marketing; User Generated Content; Purchase Decision; TikTok